EP506 The role of lymphovascular space invasion to define risk groups of endometrial cancer. (1st November 2019) - Demirkiran, F; Bese, T; Gokmen, S; Kayan, BO; Acikgoz, AS; Kahramanoglu, I; Turan, H; Arvas, M
Abstract : Introduction/Background: The main objective of this retrospective study was to define risk groups to identify patients at risk of recurrence who may benefit from adjuvant treatment. Methodology: Patients who had complete staging surgery for endometrial cancer on between 2000 and 2017 in Istanbul University-Cerrahpasa were analyzed. Patients were divided into groups according to grade of the disease and myometrial invasion (MI). Results: A total of 895 patients were identified. The presence of lymphovascular space invasion (LVSI) increased the risk of nodal involvement and decreased 5-year DFS, significantly in each group (table 1). Patients with grade 1–2 disease and no LVSI had less than 4% nodal involvement and more than 91% 5-year DFS (Group I and III). However, the presence of LVSI increased the risk of nodal involvement and recurrence significantly in patients with grade 1–2 disease (Group II and IV). Similarly, LVSI increased the risk of nodal involvement and worsen DFS in patients with grade 3 disease (Groups V to VIII). Conclusion: Along with grade and MI, LVSI is a significant factor for predicting nodal involvement. Patients having grade 1–2 tumor with <50% MI and no LVSI should be defined as low risk group. Low-intermediate risk group may be consisted of grade 3 tumor with MI of <50% and no LVSI; or grade 1–2 tumor with MI of <50% and (+) LVSI; or tumor with any grade, deep MI and no LVSI. Those with LVSI (+) tumors having deep MI and tumor grade of 1–2, or with LVSI (+) tumors with <50% MI and high grade histology can be classified as high-intermediate risk group. High-risk group should be consisted of patients with deep MI, grade 3 disease and (+) LVSI. Disclosure: Nothing to disclose.